Random walk tests for the Lisbon stock market - Borges, Maria Rosa (2022)
This article reports the results of tests on the weak-form market efficiency applied to the PSI-20 index prices of the Lisbon stock market from January 1993 to December 2006. As an emerging stock market, it is unlikely that it is fully information-efficient, but we show that the level of weak-form efficiency has increased in recent years. We use a serial correlation test, a runs test, an Augmented Dickey–Fuller (ADF) test and the multiple variance ratio test proposed by Lo and MacKinlay (1988) for the hypothesis that the stock market index follows a random walk. Nontrading or infrequent trading is not an issue because the PSI-20 includes only the 20 most traded shares. The tests are performed using daily, weekly and monthly returns for the whole period and for five sub periods which reflect different trends in the market. We find mixed evidence, but on the whole, our results show that the Portuguese stock market index has been approaching a random walk behaviour since 2000, with a decrease in the serial dependence of returns.